Turkey, the melting Pot of the West and East: an evaluation of the benefits of Western and Eastern civilizations for this adaptive nation - Abdullah @ Chuah Hock Leng, Osman (IJASSH, 2013)
This paper is about the historical absorption of quality culture from Islam and secular ways. Turkey is located in a very strategic position between east and west. In the Ottoman empire time it was able to absorb the quality culture to split Islam but when the empire declines it is able to absorb the quality of the western civilization. This research covers the historical development of Turkey acquiring the quality of other civilizations.